Chapter Conclusions - Gasparri, Stefano (Reti Medievali E-Book, 2022)
The research on the influence of the memory of the Goths and Theoderic on Carolingian rule, particularly in Italy, is just beginning. The first promising results, presented in the volume, on the knowledge of the Variae and Theoderic's Edict in the Carolingian and post-Carolingian period are highlighted, as well as the possible developments of comparative research on the origines gentium or on the various histories that circulated in the writings of the authors of the Carolingian period. Finally, bearing in mind the role of cultural mediator played by Paul the Deacon, the importance of the Lombard phase in the transmission of the memory of Ostrogothic rule to the Carolingians emerged, through a parallel between the actions of Aistulf and Charlemagne.